Inductively coupled plasma dry etching process on planar lightwave circuit fabrication / Chuah Khoon Seah - Chuah, Khoon Seah (2010)
The main objective of this project is to master state-of-the-art techniques and knowledge in silica etching in order to achieve high quality waveguide circuit on Planar Lightwave Circuit devices. Another objective is to optimize the clean room research strength, surface characterization, microscopy techniques and similar semiconductor manufacturing processes.Initially, these processes were conducted with wet etching method that utilized diluted hydrofluoric acid (HF) and buffered oxide etch (BOE). Several problems arising such as mask peel-off, poor sidewall profile and defect waveguide channel during the pattern transfer process due to its’ isotropic nature. Alternatively, dry etching method was conducted via Inductively Coupled Plasma (ICP)etch system due to the failure of wet type silica etching process. For gases selection, a mixture of Tetrafluoromethane/Argon (CF4/Ar), Tetrafluoromethane (CF4) was compared with Hexafluoroethane (C2F6). C2F6 gas was found to be the most suitable etch gas for PLC silica etching by evaluating the good waveguide channel profile and selectivity. From the results obtained, the highest etch rate of about 226 nm/min was achieved at ICP power of 1000 W, Bias power of 60 W, process pressure and gas flow rate of 10 mTorr and 35 sccm, respectively.Otherwise, process condition of ICP silica etching at ICP power of 500 W, Bias power of 60 W, process pressure of 10 mTorr, gas flow rate of 35 sccm and etch duration of 30 minutes resulted in the highest selectivity of silica to chromium mask of about 63. For overall optimum process condition of ICP silica etching, etch rate of about 192 nm/min and selectivity of about 23 was obtained at ICP power of 900 W, Bias power of 60 W, process pressure and C2F6 flow rate of 10 mTorr and 40 sccm respectively for 30 minutes duration.